Marketing effektiveness in islamic financial cooperative: a case study - Nugraha, Zulfy Bagja; Nasution, Reza Ashari (SBM ITB, 2010)
Cooperative is a model of kinship economic form in Indonesia which supported by national constitution. As a 'Muslim majority country', value of Islamic religion brought to every segment of life, including cooperative as an economic form based on kinship. Islamic Financial cooperative was a role model of religious based of alternative kinship economic form, and their existence supported by government and cause of high growth in amount. This study tries to find role model of Islamic financial cooperative of marketing effectiveness through study case. The Subject of this study was an Islamic financial cooperative (BMT) in Bandung city, Indonesia. This study was meant to be explanatory, using case study approach in one of the Islamic Financial cooperative, well known as Baytul Maal wat tamwil (BMT), used to explain factors that creating marketing effectiveness and marketing metrics that can be implemented in this form of economic. The factors was based on Kotler (1977) and Carson (1990) marketing effectiveness theory, as for marketing metrics proposed to be used as a measurement; based on Hooley & Lynch (1984), Ambler (2004). Marketing effectiveness in this study viewed as ability of organization to attain their objectives, how was the process of marketing effectiveness achieved in Islamic financial cooperative. The factors of marketing effectiveness used was proposed by Carson, which are : limitations of marketing expenditure, marketing expertise, and marketing impact; Marketing planning vs. operation, levels of generalization, marketing planning adapted to small firm, stages of marketing, level of activity. This study academically open up conditions of marketing effectiveness in Islamic financial cooperative that rarely explore.Keywords : Islamic Financial Cooperative, Marketing Effectiveness, Marketing Metric